AL 'ALAAQAH BAINA ISTII'AABI AL ASHWAT AL 'ARABIYYAH LADAA ATH THALIBAAT WA QUDRATIHINNA FII FAHMI AL MASMUU' - Maya Sari (Universitas Islam Negeri Mataram, 2022)
The questions from this research are: Is there a relationship between the students comprehension of Arabic sounds and their ability to comprehend audio for the third secondary grade at Ma’had Ulun Nuha, Medan Johor. This research aims to find out the relationship between female students' comprehension of Arabic sounds and their ability to comprehend listening for the third secondary grade at Ma’had Ulun Nuha, Medan Johor. The research methodology used is quantitative field research with relational type, and the data analysis method used is a statistical method with the symbol Rank Order. The result of this research was that the result of the relationship between female students’ comprehension of Arabic sounds and their ability to understand listening for the third secondary grade at Ma’had Ulun Nuha, Medan Johor is 0.468, which indicates that the relationship between them is moderate or moderate in a positive way. And knew that the commutative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Finally, knew that there was a relationship between the two variables.